STRATEGI PENANGANAN PERMUKIMAN KUMUH MELALUI PEMBANGUNAN RUMAH SUSUN DI SURABAYA - Nur Wulan Suci (Universitas Sains dan Teknologi Komputer, 2022)
Settlements are factors that must exist in human life in order to meet the needs of a decent quality of life for a good future. Whereas a slum is a place where it is not worth living in by someone with all its shortcomings. The purpose of this study is to provide an understanding of strategies in dealing with slums in the city of Surabaya with an effort to slightly reduce existing slums. This research uses the method of collecting primary survey data with qualitative analysis methods and through a phenomenological approach and the data used are secondary data derived from auxiliary media such as books, journals, theses, as well as from previous researchers. Then this research produces various strategies in dealing with the existence of slums with efforts to be able to deal with the existence of slums. These strategies include restoration, rejuvenation, and resettlement where from this strategy to create flats as the final result in which there are adequate facilities and infrastructure for residents who want to live there. To be able to live there, you don't need to struggle just by using a gadget and looking for the official website called SIM RUSUN, then anyone can access it. Keywords: Slums, Strategy, Flats